Characterisation of weldability and metallurgical stability of dissimilar metal welds - Bin Azahari, Ahmad Azli (2020)
Many industrial sectors require the joining of dissimilar metals, including the power plant industry where the different parts of a power plant are made of different materials due to differing requirements. The locations where the dissimilar steels or alloys are joined are termed dissimilar metal welds (DMWs). It is generally known that a significant percentage of DMWs can fail prematurely in service as a result of both primary system loads and constraints introduced due to differences in the coefficient of thermal expansion across the joint, as well as metallurgical compatibility issues.